2013
DOI: 10.1029/2012jc008073
|View full text |Cite
|
Sign up to set email alerts
|

Observations and modeling of steep‐beach grain‐size variability

Abstract: [1] Novel observations of surface grain-size distributions are used in combination with intra-wave modeling to examine the processes responsible for the sorting of sediment grains on a relatively steep beach (slope = 1:7.5). The field observations of the mean grain size collected with a digital camera system at consecutive low and high tides for a 2 week period show significant temporal and spatial variation. This variation is reproduced by the modeling approach when the surf zone flow-circulation is relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 51 publications
3
55
0
3
Order By: Relevance
“…Benthic streaming may increase entry of zooplankton into the surf zone at the RSZ, where only demersal taxa, including harpacticoid copepods, juvenile parasitic isopods seeking host shrimp and cyprids were more abundant inside than outside the surf zone. Streaming is suppressed by breaking waves at the seaward edge of the surf zone, but zooplankton, detritus and sediments near the bottom enter the surf zone by entrainment into breaking waves [25][26][27]. Although some species of cyprids have been reported to be more abundant near the sea surface [28][29][30], we previously demonstrated that cyprids of all species recruited almost entirely to the bottom of moorings just outside the surf zone over 5 years on this coast [31].…”
Section: Discussionmentioning
confidence: 99%
“…Benthic streaming may increase entry of zooplankton into the surf zone at the RSZ, where only demersal taxa, including harpacticoid copepods, juvenile parasitic isopods seeking host shrimp and cyprids were more abundant inside than outside the surf zone. Streaming is suppressed by breaking waves at the seaward edge of the surf zone, but zooplankton, detritus and sediments near the bottom enter the surf zone by entrainment into breaking waves [25][26][27]. Although some species of cyprids have been reported to be more abundant near the sea surface [28][29][30], we previously demonstrated that cyprids of all species recruited almost entirely to the bottom of moorings just outside the surf zone over 5 years on this coast [31].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we neglected potential entrainment of particles in the breaking wave roller (Feddersen 2007;Reniers et al 2013), which may contribute to the preferential transport of surface material from the shoals to the rip channels that experience less wave breaking due to their increased depth, but at present cannot be resolved within our three-dimensional modeling approach.…”
Section: Methodsmentioning
confidence: 99%
“…Cette hétérogénéité est étudiée au moyen d'une approche multi-classe multi-couche basée sur les travaux de RENIERS et al (2013). La première conséquence de l'utilisation de cette approche par rapport au cas d'un sédiment à granularité constante est la diminution des vitesses de migration (ou vitesses d'évolution du fond) au cours des simulations, dans un cas simple de migration d'une dune hydraulique en 1D sous l'action d'un courant stationnaire, ainsi que dans celui de l'évolution d'un banc de sable estuarien modélisée en 2DH et soumis à l'action de la marée.…”
Section: Discussionunclassified